2017
DOI: 10.1073/pnas.1704351114
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation and ubiquitination reciprocally regulate α-synuclein degradation and pathological aggregation

Abstract: α-Synuclein accumulation is a pathological hallmark of Parkinson's disease (PD). Ubiquitinated α-synuclein is targeted to proteasomal or lysosomal degradation. Here, we identify SUMOylation as a major mechanism that counteracts ubiquitination by different E3 ubiquitin ligases and regulates α-synuclein degradation. We report that PIAS2 promotes SUMOylation of α-synuclein, leading to a decrease in α-synuclein ubiquitination by SIAH and Nedd4 ubiquitin ligases, and causing its accumulation and aggregation into in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
163
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 47 publications
(63 reference statements)
1
163
0
2
Order By: Relevance
“…A proportion of Lewy bodies in nigral neurons stain positive for SUMO1 (Rott et al . ), suggesting a role of this modification in Parkinson's pathogenesis. Some studies demonstrated increased α‐Syn aggregation by SUMOylation upon proteasomal inhibition (Kim et al .…”
Section: Role Of Post‐translational Modifications In α‐Syn Clearancementioning
confidence: 95%
See 1 more Smart Citation
“…A proportion of Lewy bodies in nigral neurons stain positive for SUMO1 (Rott et al . ), suggesting a role of this modification in Parkinson's pathogenesis. Some studies demonstrated increased α‐Syn aggregation by SUMOylation upon proteasomal inhibition (Kim et al .…”
Section: Role Of Post‐translational Modifications In α‐Syn Clearancementioning
confidence: 95%
“…The SUMO ligase PIAS2 promoted SUMOylation of α‐Syn, which in turn reduced α‐Syn ubiquitination by SIAH and NEDD4 ubiquitin ligases and increased aggregation and α‐Syn release from the cells (Rott et al . ). In this context, it was previously shown that SUMOylation utilizes the ESCRT complex to sort α‐Syn into extracellular vesicles for secretion (Kunadt et al .…”
Section: Role Of Post‐translational Modifications In α‐Syn Clearancementioning
confidence: 97%
“…The protective effect of sumoylation is thought to be due to the enhancement of protein solubility, a finding consistent in studies of many aggregation-prone proteins [94]. In contradiction to these findings, an in vitro study linked sumoylation to impaired α - synuclein ubiquitination and reduced proteasomal degradation [95]. Increased sumoylation was also associated with α-synuclein aggregation in postmortem human brain samples [95].…”
Section: Posttranslational Modifications Of α-Synucleinmentioning
confidence: 91%
“…In contradiction to these findings, an in vitro study linked sumoylation to impaired α - synuclein ubiquitination and reduced proteasomal degradation [95]. Increased sumoylation was also associated with α-synuclein aggregation in postmortem human brain samples [95]. These contradictory findings highlight the need for further exploration of the role of sumoylation in PD pathogenicity.…”
Section: Posttranslational Modifications Of α-Synucleinmentioning
confidence: 99%
“…Rott et al filled this gaping knowledge gap by identifying SUMOylation as a major regulator of α‐synuclein degradation and pathological accumulation. They demonstrated that SUMOylation increases α‐synuclein by 2 mechanisms: (1) α‐synuclein is SUMOylated by PIAS2, which leads to α‐synuclein accumulation, aggregation, and increased levels; and (2) α‐synuclein ubiquitination via SIAH and Nedd4 is blocked, leading to further aggregation.…”
mentioning
confidence: 99%